Kelengkapan Entry Data Sosial Pasien Baru Rawat Jalan di Rumah Sakit Umum Pusat Nasional Dr. Cipto Mangunkusumo - Joko Widhi (MEDICORDHIF Jurnal Rekam Medis, 2015)
ABSTRACT In hospitals, the beginning of patient registration service, begins with the filling of personal data or patient's social data.. The registration process at Cipto Mangunkusumo National General Hospital runs according to a predetermined systemsThe formulation of this research problem is how the level of completeness of social data filling of new outpatient at National General Hospital Dr. Cipto Mangunkusumo. This research method is done by using descriptive research. Based on the results of the completeness study of the contents of the new outpatient social identity form, the lowest patient identification is 0% family name, 0% email / adress, 0% name and patient relationship, 0% identity number, for Kecamatan is 7,5% And Kelurahan is 10%. Officers have done the work in accordance with the specified path and SOP, it's just the plotting system is not displayed near the TPPRJ, the system also already facilitate the officer, the meaning of the completeness of the social data containing the Name, Address, Place and date of birth, and Phone Number, the problems that occurs frequently at the time of entry is Computers sometimes doesn’t work. Suggestions include: 1. The systems is displayed near the new outpatient registration site, 2. Patient Registration Place should be under the Medical Record Unit, 3. For certain points there is a category locking system that is considered important. Such as identity / identity cards, name & patient relationships, nationality, and surname, Keywords: completeness of new outpatient social data entry data ABSTRAK Di rumah sakit yang menjadi awal pelayanan adalah pendaftaran pasien dimulai dengan pengisian data pribadi atau data sosial pasien. Proses pendaftaran di Rumah Sakit Umum Pusat Nasional Cipto Mangunkusumo berjalan sesuai alur yang sudah ditetapkan. Rumusan masalah penelitian ini adalah bagaimanakah tingkat kelengkapan pengisian data sosial pasien baru rawat jalan di Rumah Sakit Umum Pusat Nasional Dr. Cipto Mangunkusumo. Metode penelitian ini dilakukan dengan penelitian deskriptif. Berdasarkan hasil penelitian kelengkapan isi formulir identitas sosial pasien baru rawat jalan, identifikasi pasien yang paling rendah kelengkapannya adalah nama keluarga 0%, email/adress 0%, nama dan hubungan pasien 0%, nomer identitas/KTP 0%, kecamatan 7,5% dan kelurahan 10%. petugas sudah melakukan pekerjaan sesuai dengan Alur dan SPO yang ditentukan, hanya saja alur tidak dipajang dekat dengan TPPRJ, sistemnya pun sudah memudahkan petugas, arti kelengkapan data sosial yaitu berisi Nama, Alamat, TTL, dan Nomer Telpon, kekurangan yang dirasakan pada saat entry, komputer terkadang mati. Saran antara lain: 1. Alur dibuat dan dipajang dekat dengan tempat pendaftaran pasien baru rawat jalan, 2. Sebaiknya Tempat Pendaftaran Pasien ada dibawah Unit Rekam Medis, 3. Untuk poin-poin tertentu ada sistem penguncian kategori yang dianggap penting. Seperti nomer identitas/KTP, nama & hubungan pasien, kewarganegaraan, dan nama keluarga, Kata Kunci: kelengkapan entry data sosial pasien baru rawat jalan